Adding value to eccentrics: A review of adjunctive therapies for mid-portion Achilles tendinopathy based on randomized controlled trials - Stanisław Kasprzak; Karolina Kasprzak; Laura Loryś; Klaudia Klimczak; Jakub Kamiński; Marcin Narloch; Aleksandra Wiśniewska; Małgorzata Kuczek (Medical Research Journal)
INTRODUCTION: Achilles tendinopathy is a prevalent musculoskeletal condition that affects both athletes and non-athletes, leading to pain, swelling, and impaired tendon function. It is classified into insertional and mid-portion tendinopathy, depending on its anatomical location. While eccentric exercises are the primary treatment, additional therapies may enhance outcomes. This review explores effective adjuncts to optimize eccentric exercise therapy for mid-portion Achilles tendinopathy. MATERIAL AND METHODS: A systematic search was conducted in the PubMed database for randomized controlled trials published in the last 10 years, focusing on adjunctive treatments to eccentric exercises for mid-portion Achilles tendinopathy. This review followed a structured approach inspired by Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 (PRISMA) guidelines to enhance transparency, although it does not fulfill the full criteria of a systematic review. RESULTS: Six studies met the present inclusion criteria, each focusing on a different method. High-volume injection (HVI) appears to be a safe and potentially effective short-term adjunct, particularly when combined with corticosteroids. Glyceryl trinitrate and specific collagen peptide supplementation may offer low-risk benefits, though current evidence remains limited. Photobiomodulation and Ultrasound-guided Galvanic Electrolysis Technique require further high-quality trials before clinical recommendations can be made. Platelet-rich plasma is not currently supported as a standardized treatment, though repeated application may warrant further investigation. Foot orthoses have not demonstrated consistent benefits when combined with eccentric training. CONCLUSIONS: Eccentric exercise remains the foundation of Achilles tendinopathy treatment. Among the adjunctive reviewed, HVI offers the most promising short-term results, while the efficacy of other modalities remains uncertain.